Leadership matters in MBN implementation highlights of case studies - Bautista, Victoria A. (1999)
Leadership studies focusing on the dynamics involved in leader-citizen relations have been sparse. In the context of implementing the Minimum Basic Needs (MBN) Approach, several recently concluded case studies have been integrated to document the dynamics involved in the barangay captains' advocacy of the Approach in their respective localities. In the process, profiles of successful local leaders have been synthesized along with the factors that enable or hinder the successful implementation of the MBN approach. Learnings from the case studies have also been called, from which recommendations have been drawn.
Keywords: Basic needs -- Case studies -- Barangay Pantig; Basic needs -- Case studies -- Eastern Samar; Basic needs -- Case studies -- Masbate; Basic needs -- Case studies -- Oriental Mindoro; Comprehensive and Integrated Delivery of Social Services (CIDSS); Leadership; Social Reform Agenda (SRA)